(untitled) (Journal of the College of Basic Education, 2022)
The paper presents a developed method with algorithms written in Matlab language to find the numerical solution of nth-order state-space equations (SSE) of linear continuous-time control system by using Scraton method. State-space equation is the modern representation to analysis continuous-time system. It was treated numerically to the single-input-single-output (SISO) systems as well as multiple-input-multiple-output (MIMO) systems by using fourth-order Scraton method. Scraton method employed to find the output values of the state-space equations. Comparisons between the numerical and exact results are given for some numerical examples to conciliate the accuracy of the proposed method.